2015
DOI: 10.1371/journal.pone.0143599
|View full text |Cite
|
Sign up to set email alerts
|

Family Health Climate and Adolescents’ Physical Activity and Healthy Eating: A Cross-Sectional Study with Mother-Father-Adolescent Triads

Abstract: IntroductionThe importance of the family environment for children’s and adolescents’ health behavior has been demonstrated, the underlying mechanisms of this influence remain unclear. Therefore, the aim of the study was to investigate the relationship between family environmental and individual determinants. It was hypothesized that the Family Health Climate (FHC) is associated with adolescents’ physical activity and dietary behavior and that intrinsic motivation mediates this association.MethodsCross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 63 publications
(63 reference statements)
9
47
0
Order By: Relevance
“…The first study was a validation study of the FHC instrument [ 20 ]. In the second study, FHC showed to be associated with adolescents’ physical activity behavior and nutrition behavior and they found that this was mediated by adolescents’ intrinsic motivation [ 21 ]. The current study was the first to investigate the link between FHC (in this case FNC) and parental measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study was a validation study of the FHC instrument [ 20 ]. In the second study, FHC showed to be associated with adolescents’ physical activity behavior and nutrition behavior and they found that this was mediated by adolescents’ intrinsic motivation [ 21 ]. The current study was the first to investigate the link between FHC (in this case FNC) and parental measures.…”
Section: Discussionmentioning
confidence: 99%
“…This variable is assumed to affect the health behavior of all family members and has been operationalized by a scale measuring the family physical activity climate and a scale measuring the family nutrition climate (FNC). The FNC was found to be associated with adolescents’ consumption of fruit, vegetables and salad [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FHC is a family level variable reflecting an aspect of the shared family environment ( 62 , 63 ). It is defined as the shared perceptions and cognitions concerning a healthy lifestyle within a family.…”
Section: Methodsmentioning
confidence: 99%
“…Obesogenic behaviours, including high screen time [1,2], consumption of sugar sweetened beverages (SSBs) [3,4] and lack of sleep [5,6] have become more prevalent in children and adolescents in recent years. In addition to age, socioeconomic status (SES), sex [7,8] and parental education [7,9], the family environment has a major influence on children's and adolescent's behaviour [10]. Parents often serve as role models for their children and their parenting style, including family rules and routines, may affect their children's obesity-related behaviours [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%